Prognostic Factors for Survival in Patients with Carcinoma Endometrium - Prakasan, Aparna Mullangath; Dhas, Minolin; Jagathnathkrishna, Krishnapillai M.; Kumar, Aswin; Mathews, Susan; Joseph, John; Sambasivan, Suchetha; James, Francis V. (South Asian Journal of Cancer, 2022)
Objective The study aimed to see the clinical outcome and to identify prognostic factors for survival in patients with carcinoma endometrium.Methods Patients registered at Regional Cancer Centre, Thiruvananthapuram, Kerala, India, with carcinoma endometrium from January 2009 to December 2013 were identified from hospital registry. Data regarding patient demographics, tumor characteristics, treatment schedules, and follow-up were collected using a structured proforma. Survival estimates were generated using the Kaplan–Meier method. Univariate analysis was done using chi-square and Fisher's exact tests. Multivariate analysis using the Cox regression model was performed to determine the impact of prognostic factors on outcome. The statistical analysis was done using SPSS software version 11.Results The median follow-up of the 686 patients was 95 months (range 3–178 months).There were 432 stage 1 (63%), 100 stage II (14.6%), 108 stage III (15.7%), and 46 stage IV patients (6.7%). The 5-year overall survival was 89.2%. Prognostic factors for survival on univariate analysis were age 60 years or older, nonendometrioid histology, high-grade tumor, cervical stromal involvement, para-aortic node involvement, negative progesterone receptor expression, deep myometrial invasion advanced stage, surgery versus no surgery, serosal involvement, and ovarian and fallopian tube involvement. However, on multivariate analysis, age over 60 years, higher histological grade, advanced stage, and deep myometrial and parametrial invasion were associated with significantly poorer survival.Conclusion We found that age over 60 years at presentation, higher grade, advanced stage, deep myometrial invasion, and parametrial invasion were associated with poorer survival.
Keywords: prognosis; radiotherapy; surgery; survival; uterine neoplasms